Improving Student Learning Outcomes Through Accurate Online Modules with the ADDIE Model - Dilaines, Linanda Elsa; Astuti, Elly; Yusdita, Elana Era (Universitas Pendidikan Ganesha, 2024)
Accurate online is one of the applications used in accounting learning. This course is mandatory so that students have adaptive skills in the digital era. However, the available reference sources could be more extensive. The impact is that students only memorize example questions from the lecturer and need clarification when faced with other model questions. This research aims to develop an accurate online module as an additional reference for student learning. The development model used is the ADDIE model, which consists of 5 stages: Analysis, Design, Development, Implementation, and Evaluation. The development focus is on sales material because it is the most significant business development sector. The research results show that the Accurate Online Sales Feature module was declared feasible in validation tests from material, language, and graphic design experts. The Accurate Online Sales Feature module is reasonably practical and can improve student learning outcomes in computer accounting learning. The Accurate Online module, equipped with illustrations and case studies, can accommodate students with visual and kinesthetic learning styles.